WHOse Health?: A Critical Analysis of the World Health Organization Definition of Health - Goto, Ayumi (My University, 2000)
This thesis offers a critical analysis of the World Health Organization (WHO) definition of health. Feminist epistemology is used to reveal how health and disease are dualistically constructed. Beyond serving as designations for different physiological statuses, these terms are of metaphorical significance, such that individuals affiliated with 'health' are socio-economically, politically and effectively morally preferred over those associated with 'disease'. Popular and immunological conceptions of 'disease' provide justifications for maintaining the oppression of the latter identity. Given WHO's history of prioritizing disease control over primary health care and the consequent implementation of both objectives within a disease-oriented framework, WHO's definition of health is in danger of supporting the health/disease dualism, which in turn jeopardizes the organization's mandate to treat its members formally and substantively equally, and to provide 'health for all'.
Whose Health?: A Critique of WHO's Definition of Health
Keywords: health; definition; WHO; world; analysis